Effects of soy milk consumption on gut microbiota, inflammatory markers, and disease severity in patients with ulcerative colitis: a study protocol for a randomized clinical trial - Sadeghi, Omid (Trials, 2020)
BACKGROUND: Several strategies are recommended to alleviate clinical symptoms of ulcerative colitis (UC). Soy milk may affect UC through its anti-inflammatory properties. However, no study has examined the effects of soy milk consumption on gut microbiota and inflammatory biomarkers in patients with UC. The current study will be done to examine the effects of soy milk consumption on UC symptoms, inflammation, and gut microbiota in patients with UC. METHODS: This study is a randomized clinical trial, in which thirty patients with mild to moderate severity of UC will be randomly allocated to receive either 250 mL/day soy milk plus routine treatments (n = 15) or only routine treatments (n = 15) for 4 weeks. Assessment of anthropometric measures and biochemical indicators including serum concentrations of high-sensitivity C-reactive protein (hs-CRP), tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and interferon gamma (IFN-γ) will be done at the study baseline and end of trial. In addition, the quantity of butyrate-producing bacteria including Clostridium cluster IV, Faecalibacterium prausnitzii, and Roseburia spp.; prebiotic bacteria including Lactobacillus spp. and Bifidobacteria spp.; and mucus-degrading bacteria including Akkermansia muciniphila, Bacteroides fragilis, and Ruminococcus spp., as well as calprotectin and lactoferrin levels, will be explored in fecal samples. Also, the Firmicutes to Bacteroidetes ratio which is of significant relevance in human gut microbiota composition will be assessed. DISCUSSION: Altered gut microbiota has been reported as an important contributing factor to inflammation in patients with inflammatory bowel disease (IBD). Soy milk contains several components such as phytoestrogens with potential anti-inflammatory properties. This product might affect gut microbiota through its protein and fiber content. Therefore, soy milk might beneficially affect systemic inflammation, gut microbiota, and then clinical symptoms in patients with UC. TRIAL REGISTRATION: Iranian Registry of Clinical Trials (www.irct.ir) IRCT20181205041859N1. Registered on 27 January 2019.